MENULIS TEKS CERITA PENDEK BERBANTUAN MEDIA GAMBAR BERSERI SISWA KELAS VII SMP ISLAM KHAIRA UMMAH PADANG - Helda, Trisna (Universitas PGRI Sumatera Barat, 2017)
Abstract: This research is motivated by the limitations of students in writing and developing short stories and less media to support students in the learning process of short story writing. The purpose of this study is to describe the ability to write text short stories of students kelsi VII SMP Islam Khaira Ummah Padang assisted media images glow. This type of research is classified as quantitative research using descriptive method. The population of the study were the seventh grade students of Islamic Junior High School Khaira Ummah Padangyang registered in 2015/2016 academic year, as many as 135 people spread in 5 classes. The sampling technique used is purposive sampling. The number of samples of this study as many as 22 students are students of class VIIB. The data of this research is the result of writing test of short story text of VII students of SMP Islam Khaira Ummah Padang. Based on the results of the study of the ability to write short story text students of the seventh grade of Islamic Junior High School Khaira Ummah Padang with the help of a series of images for the whole with the average of 83.71 counts are good in the range of 76-85%. Keywords: short story text, images beamedAbstrak: Penelitian ini dilatarbelakangi oleh keterbatasan siswa dalam menulis dan mengembangkan cerita pendek dan kurangya media untuk mendukung siswa dalam proses pembelajaran menulis cerita pendek. Tujuan penelitian ini adalah mendeskripsikan kemampuan menulis teks cerita pendek siswa kelsa VII SMP Islam Khaira Ummah Padangberbantuan media gambar berseri.Jenis penelitian ini tergolong penelitian kuantitatif dengan menggunakan metode deskriptif.Populasi penelitian adalah siswa kelas VII SMP Islam Khaira Ummah Padangyang terdaftar pada tahun ajaran 2015/2016, sebanyak 135 orang yang tersebar dalam 5 kelas.Teknik pengambilan sampel yang digunakan yaitu purposive sampling.Jumlah sampel penelitian ini sebanyak 22 orang siswa yaitu siswa kelas VIIB. Data penelitian ini berupa hasil tes menulis teks cerita pendek siswa kelas VII SMP Islam Khaira Ummah Padang. Berdasarkan hasil penelitian kemampuan menulis teks cerita pendek siswa kelas VII SMP Islam Khaira Ummah Padangberbantuan media gambar berseri untuk keseluruhan dengan rata-rata hitung 83,71 tergolong baik berada pada rentangan 76-85%. Kata kunci:teks cerita pendek, gambar berseri